2016
DOI: 10.1177/1362361316635826
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an employer-based intervention on employment outcomes for youth with significant support needs due to autism

Abstract: The purpose of this study was to develop and investigate an employer-based 9-month intervention for high school youth with autism spectrum disorder to learn job skills and acquire employment. The intervention modified a program titled Project SEARCH and incorporated the use of applied behavior analysis to develop Project SEARCH plus Autism Spectrum Disorder Supports. A randomized clinical trial compared the implementation of Project SEARCH plus Autism Spectrum Disorder Supports with high school special educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 32 publications
2
116
0
1
Order By: Relevance
“…An interview skills group RCT used waitlist control (Morgan et al, 2014). The remaining five RCTs included were all compared to no-treatment groups (Hayes et al, 2015;Smith et al, 2014;Strickland et al, 2013;Wehman et al, 2014;Wehman et al, 2016b).…”
Section: Employment Programs and Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…An interview skills group RCT used waitlist control (Morgan et al, 2014). The remaining five RCTs included were all compared to no-treatment groups (Hayes et al, 2015;Smith et al, 2014;Strickland et al, 2013;Wehman et al, 2014;Wehman et al, 2016b).…”
Section: Employment Programs and Interventionsmentioning
confidence: 99%
“…The remaining studies reported increased job placement and retention for individuals with ASD following intensive work-training programs and job coaching. Overall, jobs were retained from between 6 and 30 months, wages earned ranged between US $5.01-$18 and an average of 25.45 hours/week were worked (Burt et al, 1991;Ham et al, 2014;Hillier et al, 2007;Wehman et al, 2013;Wehman et al, 2014;Wehman et al, 2016b;Baker-Ericzen et al, 2018;McLaren et al, 2017).…”
Section: Employment Statusmentioning
confidence: 99%
“…[9][10][11][12][13] Despite these obstacles, multiple studies show that it is possible to improve employment outcomes of TAY-ASD when effective services are provided. [14][15][16] Vocational rehabilitation (VR) is one of the key sources of public assistance for people with disabilities in the United States who seek employment. The U.S. Department of Education's Rehabilitation Services Administration (RSA) provides grants to states to operate VR agencies in accordance with federally approved state plans for the implementation of VR services.…”
Section: Introductionmentioning
confidence: 99%
“…If employers are to fulfill their responsibilities of creating inclusive work environments by enhancing employment opportunities and effectively providing support for individuals on the autism spectrum, then employer education is critical in developing the pre-requisite attitudes and self-efficacy beliefs (Kaye et al 2011;Unger and Kregel 2003;Sheeran et al 2016). Employers are currently an under supported and overlooked resource in the work environment (Erickson et al 2014), with a paucity of studies exploring employers' capacity to support individuals on the autism spectrum (Unger 2007;Hagner and Cooney 2003;Rashid et al 2017;Wehman et al 2016). In response to the need to address limitations in current approaches to disability employment support for autism and enhance employers' skills in hiring and supporting individuals on the autism spectrum, the Integrated Employment Success Tool (IEST TM ) was developed.…”
Section: Introductionmentioning
confidence: 99%